IMPROVING STUDENTS’ VOCABULARY THROUGH AUDIO-VISUAL BY USING YOUTUBE VIDEOS AT SMA NEGERI 2 TONDANO - Valentino Tamara; Nihta V. F. Liando; Ignatius J. Tuerah (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this study was “to find out whether or not the use of audio visual by YouTube videos improves vocabulary”. This research was used quantitative research through pre-experimental research with one group pre-test and post-test design. Pre-test was a test which is given to the students before treatment. And post-test was a test which is given after treatment. There were 2 tests: T1 was the pre-test and T2 was post-test. X is used symbolize the treatment. This research was conducted SMA Negeri 2 Tondano especially tenth grade students (one class only). This school was used K-13 as their curriculum. After conducting the research, it could be concluded that the use audio visual by YouTube videos as the learning method to improve students’ vocabulary mastery is an effective way to solve the problem, when before applying the treatment they are lack in vocabulary mastery, especially the knowledge to know the meaning of each English words, the result showed the score in the post-test is significantly high than pre-test, not only that most of the students witness how helpful this method in their English learning activity such as reading, speaking and listening. The use of audio visual by YouTube indicated successfully influence the learning outcomes from each students, because they willing to improve and improve through utilizing their hobbies in watching YouTube while at the same time they can explore their English learning preferences in a proper way